The Influence of Leadership, Organizational Commitment and Work Discipline on Organizational Citizenship Behavior (OCB) PT Harfarindo Utama Hasana - Dina Indravi Pratiwi; M. Chaerul Rizky; Halimatussa'diah (CV. Doki Course and Training, 2026)
Employee Organizational Citizenship Behavior (OCB) is an important asset for the company because it reflects a voluntary attitude in supporting organizational performance and effectiveness. This study aims to determine the influence of leadership, organizational commitment, and work discipline on Organizational Citizenship Behavior (OCB) in employees of PT Harfarindo Utama Hasana. This type of research is associative quantitative. The population in this study is all employees of the production department of PT Harfarindo Utama Hasana, with a total sample of 49 people taken using the saturated sampling technique, because all members of the population are used as samples. The data collection technique was carried out through the distribution of questionnaires, and the data was analyzed using multiple linear regression analysis with the help of SPSS software version 29. The results of the study showed that partially, leadership variables did not have a significant effect on OCB, while organizational commitment had a negative and significant effect, as well as work discipline had a positive and significant effect on OCB. Simultaneously, all three variables (leadership, organizational commitment, and work discipline) had a significant effect on OCB, with a contribution of 35.3%, while the rest were influenced by other factors outside of this study. These findings show the importance of the role of work discipline in shaping the extra behavior of employee roles in the organizational environment.